Role of Vitamin D in the Prevention of Pancreatic Cancer - Pubudu Bulathsinghala; Kostas N. Syrigos; Muhammad W. Saif (Journal of Nutrition and Metabolism)
Pancreatic cancer is a malignancy of poor prognosis which is mostly diagnosed at advanced stages. Current treatment modalities are very limited creating great interest for novel preventive and therapeutic options. Vitamin D seems to have a protective effect against pancreatic cancer by participating in numerous proapoptotic, antiangiogenic, anti-inflammatory, prodifferentiating, and immunomodulating mechanisms. 25-hydroxyvitamin D [25(OH)D] serum concentrations are currently the best indicator of vitamin D status. There are three main sources of vitamin D: sun exposure, diet,and dietary supplements. Sun exposure has been associated with lower incidence of pancreatic cancer in ecological studies. Increased vitamin D levels seem to protect against pancreatic cancer, but caution is needed as excessive dietary intake may have opposite results. Future studies will verify the role of vitamin D in the prevention and therapy of pancreatic cancer and will lead to guidelines on adequate sun exposure and vitamin D dietary intake.